Phenolic compounds profile of optimised green and eco-friendly extracts of Eugenia pyriformis leaves: an alternative for antioxidant and antibacterial applications - Dacoreggio M.V. (2023)
© 2023 Informa UK Limited, trading as Taylor & Francis Group.The Eugenia pyriformis Cambess (uvaia) is a well-known source of bioactive compounds. This study investigated the efficiency of Ultrasound-Assisted Extraction (UAE) and Enzyme-Assisted Extraction (EAE) in obtaining uvaia leaf extracts with high antioxidant and antibacterial activity. In a first step, different variables of the leaves were employed to define the best conditions for obtaining the extract with the highest total phenolic content. In a second step, the optimised extracts were characterised. In total, twenty-four phenolic compounds were identified through LC-ESI-MS/MS. The EAE in optimised conditions showed a higher amount of total phenolic compounds and antioxidant potential. It was possible to note an analogous potential of antibacterial activity of the extracts, which showed action mainly against Gram-positive bacteria. These findings suggest that the aqueous extracts of uvaia leaves are feasible, economic, and sustainable alternatives for adding value to uvaia leaves, which are an agricultural residue that is generally underutilised.